Archaeocerus uenoi n. gen. n. sp. (Coleoptera Leiodidae Catopocerinae) from Albian/Cenomanian age amber of Myanmar - Perreau, Michel (Zootaxa, 2019)
The first fossil Catopocerinae: Archaeocerus uenoi n. gen. n. sp. (Coleoptera Leiodidae) is described and figured. It comes from the upper Cretaceous (Albian/Cenomanian) amber deposit of the Hukawng valley, in northern Myanmar. Archaeocerus has developed eyes and flight wings, contrast to all the other genera of the subfamily which are anophthalm and apterous.